(untitled) (European Journal of Economics, Finance and Business Development, 2025)
In a rapidly evolving global landscape, Uzbekistan stands at a crucial juncture where strategic changes in innovation, competition, and technology are imperative for sustainable development. As the nation seeks to strengthen its economic foundation and enhance its global standing, understanding the role of these strategic shifts becomes essential.